Community-Onset Bloodstream Infection during the 'After Hours' Is not Associated with an increased Risk for Death. Issue 4 (2012) - Laupland, Kevin B; Kibsey, Pamela C; Galbraith, John C
Abstract : BACKGROUND/OBJECTIVE: Patients admitted to hospital during the 'after hours' (weekends and evenings) may be at increased risk for adverse outcome. The objective of the present study was to assess whether community-onset bloodstream infections presenting in the after hours are associated with death. METHODS: All patients in the Victoria area of British Columbia, who had first admissions with community-onset bloodstream infections between 1998 and 2005 were included. The day of admission to hospital, the day and time of culture draw, and all-cause, in-hospital mortality were ascertained. RESULTS: A total of 2108 patients were studied. Twenty-six per cent of patients were admitted on a weekend. Blood cultures were drawn on a weekend in 27% of cases and, in 43%, 33%, and 25% of cases, cultures were drawn during the day (08:00 to 17:59), the evening (18:00 to 22:59) and night (23:00 to 07:59), respectively. More than two-thirds (69%) of index cultures were drawn during the after hours (any time Saturday or Sunday and weekdays 18:00 to 07:59). The overall in-hospital case fatality rate was 13%. No difference in mortality was observed in relation to the day of the week of admission or time period of sampling. After-hours sampling was not associated with mortality in a multivariable logistic regression model examining factors associated with death. CONCLUSION: Presentation with community-onset, bloodstream infection during the after hours does not increase the risk of death.